Genetic characterization of four native Italian shepherd dog breeds and analysis of their relationship to cosmopolitan dog breeds using microsatellite markers. (6th August 2015) - Bigi, D.; Marelli, S. P.; Randi, E.; Polli, M.
Abstract : Very little research into genetic diversity of Italian native dog breeds has been carried out so far. In this study we aimed to estimate and compare the genetic diversity of four native Italian shepherd dog breeds: the Maremma, Bergamasco, Lupino del Gigante and Oropa shepherds. Therefore, some cosmopolitan dog breeds, which have been widely raised in Italy for a long time past, have also been considered to check possible influence of these dog populations on the Italian autochthonous breeds considered here. A total of 212 individuals, belonging to 10 different dog breeds, were sampled and genotyped using 18 autosomal microsatellite loci. We analyzed the genetic diversity of these breeds, within breed diversity, breed relationship and population structure. The 10 breeds considered in this study were clearly genetically differentiated from each other, regardless of current population sizes and the onset of separate breeding history. The level of genetic diversity explained 20% of the total genetic variation. The level of H E found here is in agreement with that found by other studies. The native Italian breeds showed generally higher genetic diversity compared with the long established, well-defined cosmopolitan dog breeds. As the Border Collie seems closer to the Italian breeds than the other cosmopolitan shepherd dogs considered here, a possible utilization of this breed to improve working performance in Italian traditional working shepherd dogs cannot be ignored. The data and information found here can be utilized in the organization of conservation programs planned to reduce inbreeding and to minimize loss of genetic variability.